Translating Tourist Texts Into Non-Mother Tongue: An Experiment with a Multilingual Corpus - Castillo Rodríguez, Cristina (Opción, 2016)
The aim of this paper is to carry out an experiment with semiprofessional translators, i.e., undergraduate students in their last year of their degree in Translation and Interpreting. The experiment consists of translatinginto non-mother tongue (English, French, or Italian) some text fragments written originally in Spanish so as to analyse the quality of their translations. The compilation of this multilingual corpus and its subsquent exploitation will allow us to classify the most frequent mistakes found in the translated fragments. Apart from the mistakes, we will also show the kind of resources these semi-professional translators used for their specialised translations.